GIS based chemical fate modeling : principles and applications - Pistocchi, Alberto, 1972- (Wiley, 2014)
Explains how GIS enhances the development of chemical fate and transport models Over the past decade, researchers have discovered that geographic information systems (GIS) are not only excellent tools for managing and displaying maps, but also useful in the analysis of chemical fate and transport in the environment. Among its many benefits, GIS facilitates the identification of critical factors that drive chemical fate and transport. Moreover, GIS makes it easier to communicate and explain key model assumptions. Based on the author's firsthand experience in environmental asse.